An ordered mesoporous Ag superstructure synthesized via a template strategy for surface-enhanced Raman spectroscopy. Issue 29 (6th July 2015) - Tian, Cuifeng; Li, Jiang; Ma, Chunsheng; Wang, Ping; Sun, Xiaohong; Fang, Jixiang
Abstract : Ordered mesoporous Ag superstructure was synthesized by means of a nanocasting process. The nanowire bundled superstructure shows uniform distribution of small nanogap size down to ∼2 nm, thus exhibits ultrahigh Raman enhancement. Abstract : Surface-enhanced Raman scattering (SERS) substrates with high density and uniformity of nanogaps are proven to enhance the reproducibility and sensitivity of the Raman signal. Up to now, the syntheses of a highly ordered gold or silver superstructure with a controllable nanoparticle size and a well-defined particle gap have been quite limited. Here, we reported an ordered mesoporous silver superstructure replicated by using ordered mesoporous KIT-6 and SAB-15 as templates. By means of a nanocasting process, the ordered mesoporous Ag superstructure was successfully synthesized, which shows uniform distribution of the nanowire diameter (10 nm) and nanogap size (∼2 nm), thus exhibiting a high Raman enhancement of ∼10 9 . The finite difference time-domain (FDTD) results indicate that the ordered mesoporous Ag superstructure has a uniform distribution of hot spots. Therefore, the mesoporous silica template strategy presented here could lead to a new class of high quality SERS substrates providing extraordinary potential for diverse applications.